1987
DOI: 10.1029/jb092ib11p11457
|View full text |Cite
|
Sign up to set email alerts
|

Relation of the spectroscopic reflectance of olivine to mineral chemistry and some remote sensing implications

Abstract: Using high-resolution visible and near-infrared diffuse spectral reflectance, we have systematically investigated apparent wavelength shifts as a function of mineral chemistry in the Fe/Mg olivine series from Foil to Fo91. The study also shows that trace amounts of nickel can be spectrally detected in the olivine structure. We show that significant compositional information can only be extracted at relatively high resolution, because the overall spectral characteristics of the olivines change only subtly as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
200
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(209 citation statements)
references
References 14 publications
6
200
1
Order By: Relevance
“…The relationship between these spectral parameters and the mineralogy, particularly pyroxene and olivine, has been studied in various papers over the last years (Adams 1974;King & Ridley 1987;Cloutis & Gaffey 1991;Klima et al 2007;Gaffey et al 2002). In the following section, we will discuss the different mineralogical properties of the observed asteroids as disclosed by the computed spectral parameters.…”
Section: Band Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between these spectral parameters and the mineralogy, particularly pyroxene and olivine, has been studied in various papers over the last years (Adams 1974;King & Ridley 1987;Cloutis & Gaffey 1991;Klima et al 2007;Gaffey et al 2002). In the following section, we will discuss the different mineralogical properties of the observed asteroids as disclosed by the computed spectral parameters.…”
Section: Band Parametersmentioning
confidence: 99%
“…The pyroxene composition, i.e., the molar Ca [Wo] and Fe [Fs] contents, can be obtained from the values of the absorption band centers near 1 and 2 μm using equations derived by exhaustive laboratory calibrations performed by several authors (Adams 1974;King & Ridley 1987;Cloutis & Gaffey 1991). These equations have been recompiled for pyroxenes (Gaffey et al 2002) and for HED meteorites (Burbine et al 2007) and are used here to derive the [Wo] and [Fs] contents for the observed asteroids.…”
Section: Inferred Mineralogymentioning
confidence: 99%
“…The composite 1 lm band, which is attributed to electronic transitions of Fe 2+ occupying both the M1 and M2 crystallographic sites (Burns, 1970), moves to longer wavelengths as FeO content increases (King and Ridle, 1987;Sunshine and Pieters, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…All eight asteroid band-band data plot slightly above the HED data, which suggests a possible minor contribution from olivine or a high-Ca pyroxene phase. These minerals (olivine, Type A clinopyroxene) only exhibit Band I absorption features; however, Band I centers for olivine will increase with increasing relative abundances while no band center trend is seen for Type A clinopyroxenes (King and Ridley, 1987;Burns, 1993a;Schade et al, 2004;Sanchez et al, 2014). However, any contribution from these phases will be minor as the Figure 4 data plots only slightly above the HED data and a significant contribution from another mineral phase is not apparent in Figure 3 or Figure 5.…”
Section: Pyroxene Band-band Plot Analysismentioning
confidence: 82%